Olfactory neuroblastoma (esthesioneuroblastoma) presenting as ectopic ACTH syndrome: always follow your nose. (17th October 2019) - Decaestecker, Karen; Wijtvliet, Veerle; Coremans, Peter; Van Doninck, Nike
Abstract : Summary: ACTH-dependent hypercortisolism is caused by an ectopic ACTH syndrome (EAS) in 20% of cases. We report a rare cause of EAS in a 41-year-old woman, presenting with clinical features of Cushing's syndrome which developed over several months. Biochemical tests revealed hypokalemic metabolic alkalosis and high morning cortisol and ACTH levels. Further testing, including 24-hour urine analysis, late-night saliva and low-dose dexamethasone suppression test, confirmed hypercortisolism. An MRI of the pituitary gland was normal. Inferior petrosal sinus sampling (IPSS) revealed inconsistent results, with a raised basal gradient but no rise after CRH stimulation. Additional PET-CT showed intense metabolic activity in the left nasal vault. Biopsy of this lesion revealed an unsuspected cause of Cushing's syndrome: an olfactory neuroblastoma (ONB) with positive immunostaining for ACTH. Our patient underwent transnasal resection of the tumour mass, followed by adjuvant radiotherapy. Normalisation of cortisol and ACTH levels was seen immediately after surgery. Hydrocortisone substitution was started to prevent withdrawal symptoms. As the hypothalamic–pituitary–axis slowly recovered, daily hydrocortisone doses were tapered and stopped 4 months after surgery. Clinical Cushing's stigmata improved gradually. Learning points: Ectopic ACTH syndrome can originate from tumours outside the thoracoabdominal region, like the sinonasal cavity. The diagnostic accuracy of IPSS is not 100%: both false positives and false negatives may occur and might be due to a sinonasal tumour with ectopic ACTH secretion. Olfactory neuroblastoma (syn. esthesioneuroblastoma), named because of its sensory (olfactory) and neuroectodermal origin in the upper nasal cavity, is a rare malignant neoplasm. It should not be confused with neuroblastoma, a tumour of the sympathetic nervous system typically occurring in children. If one criticises MRI of the pituitary gland because of ACTH-dependent hypercortisolism, one should take a close look at the sinonasal field as well.